Iran's Oil Wealth: Treasure and Trouble for the Shah's Regime. A Context-sensitive Analysis of the Ambivalent Impact of Resource Abundance - Miriam Shabafrouz (German Institute of Global and Area Studies (GIGA), 2009)
The Iranian revolution still appears to be a puzzle for theoretical approaches linking political instability and/or violent conflict to the resource wealth of a country. It therefore works well as a case study for the purposes of this paper: to show the necessity of a broader approach to the resource-violence link and to highlight the 'context approach'. The focus is on the violence that accompanied the events preceding the revolution, and also on the fact that this violence was mainly exercised by the rulers and - excluding the activities of militant groups - only very randomly by the masses. Many relevant contextual conditions had an impact on the downfall of the shah's regime: demographic (population growth, urbanization) and cultural factors (religious tradition, national identity); the vivid memory of several historical events; the personal preferences of central actors' mainly both the shahs - which in combination brought the country to an impasse; and the religious opposition to the regime. But upon closer examination, it becomes clear that many of those factors were influenced by resource;specific conditions such as the amount and the use of oil income, sudden oil-price drops, and external interference aimed mainly at the domination of the oil sector. It was the specific interplay of these and other contextual conditions - as much resource;specific as general, and both within the country and on an international scale - that finally brought about the downfall of the regime. – – Irans Ölreichtum: Stolz und Stolperstein für das Schahregime Eine kontextsensible Analyse der ambivalenten Auswirkungen von Ressourcenreichtum. Die iranische Revolution ist heute noch ein Rätsel für theoretische Ansätze, die politische Instabilität und/oder gewaltsame Konflikte auf den Ressourcenreichtum eines Landes zurückführen. An ihr wird die Notwendigkeit deutlich, die Verbindung zwischen Ressourcenreichtum und Gewalt in einem größeren Kontext zu sehen. Der Fokus des Artikels liegt auf der Gewalt, die die Ereignisse vor der Revolution begleitete. Mehrere Kontextbedingungen waren dabei relevant, wie zum Beispiel demografische (Bevölkerungswachstum, Urbanisierung) und kulturelle Faktoren (religiöse Traditionen, nationale Identität). Auch die kollektive Erinnerung an bestimmte historische Ereignisse und die persönlichen Präferenzen zentraler Akteure - und hier vor allem beider Schahs - haben in ihrem spezifischen Zusammenspiel das Land in eine Sackgasse und die religiöse Opposition an die Macht geführt. Die Untersuchung verdeutlicht, dass viele dieser Faktoren durch ressourcenspezifische Bedingungen beeinflusst wurden, wie z. B. die Menge und die Verwendung der Erdöleinnahmen, plötzliche Erdölpreissenkungen oder auch Einflussnahmen durch externe Akteure, die vor allem auf die Kontrolle des Erdölsektors abzielten. Es war das spezifische Zusammenspiel sowohl ressourcen-spezifischer als auch allgemeiner Kontextbedingungen, innerhalb und außerhalb des Landes, die schlussendlich den Zusammenbruch des Regimes herbei führten und zur Gewaltanwendung beitrugen.
Keywords: 300; Iran; oil; revolution; resource curse; rentier state theory; context approach; Mineralölwirtschaft; Erdölpolitik; Rent Seeking; Sozialer Konflikt; Politische Unruhen; Iran